HoneypotLabsac: um Framework de Honeypot Virtual para o Android - OLIVEIRA, Vladimir Bezerra de (2012)
Mobile devices such as Smartphones, have become indispensable nowadays, due their increased processing power, more room for data storage, batteries with greater time autonomy, connection to wireless networks and 3G networks. . The Android Operating System is a complete platform for mobile devices principally for Smartphones developed by Google in 2008. It is gaining an increasingly global market space, due to its open-source code. Attacks on mobile phones are not a current practice. The first virtual virus called Cabir, was developed in 2004, and it is concerned only the Symbian operating system. Studies show great evolution of digital attacks to the Android operating system. Honeypots (tools that have many features such as deceive the attacker) can be quite useful in the context of network security. They make the attacker think that he is actually interacting with an operating system, but in fact the attacker is being monitored. Therefore, the present thesis is aimed to develop a Framework (framework) to generate a virtual Honeypot at the level of application for the Android operating system. The methodological procedures for the preparation of this work are the: bibliography research articles, essays and literature specific.. In this work, we show that the attacker can be monitored in mobile devices through a Honeypot generated by the framework developed here in order to be used as a tool in network security based on deception. From our experience in this study, we report some essential recommendations points for improving and expanding this work.